Teknik Permainan Cello Dalam Langgam Jawa Yen Ing Tawang Ono Lintang - Septia Marga Riasetyani (Saraswati)
Java style is one type of music in Indonesia, especially in Java and a national cultural asset. Java style has characteristics similar to keroncong, among others : the number of bars, shapes, and phrases of songs. Differences with the Java style for keroncong scales used and the tecnique of playing the instrument. In terms of playing, playing cello of Java style is different with playing keroncong cello rendition. Cello playing techniques in the style of Java imitating musical instrument kendhang on the music of Java. In this paper, the writer will attempt to write patterns play cello instrument contained in the Java style song : Yen Ing Tawang Ono Lintang. The method used is qualitative. Reference sources used to obtain the data is with literature, analyzing audio recordings and video playing cello, and conducted interviews on a resource that practitiones keroncong cello. Keywords : Java style, cello playing tecniques, song yen ing tawang ono lintang.